Effects of carbohydrate ingestion on maximal sprint performance and neurohormonal responses - Fam, Kai Deng (2016)
This study investigated whether ingestion of a carbohydrate solution could improve maximal sprint cycling performance. Ten healthy males ingested 100 mL of one of the following solutions 20 min before exercise in a randomised, double-blinded order: (a) 10% (w/v) glucose solution, (b) 0.05% (w/v) aspartame solution, (c) 10.4% (w/v) maltodextrin solution, or (d) water as a control. Each participant then performed a 45-s maximal sprint effort on a cycle ergometer. Perceptual rating and blood samples were measured before and after exercise. Glucose trial was not significantly different compared to other trials across all indicators of sprint performance (relative peak and mean power output over 0-45s, 0-15s, 15-30s, and 30-45s). However, peak (3.7-3.9%) and mean power output at 0-15s (1.8-3.0%) of the sprint tended to be higher in the glucose trial compared with the maltodextrin and aspartame trials. In addition, no significant difference was found for perceptual ratings, blood lactate and plasma prolactin concentrations within trials. On the contrary, there was significant difference between glucose and maltodextrin vs. aspartame and water trials for blood glucose concentration (p < .05) and plasma insulin concentrations (p < .05). Interestingly, plasma insulin response was delayed with maltodextrin trial compared to glucose trial (p < .05). The observed improvement trend suggests that the ingestion of glucose may be meaningful and beneficial to maximal sprint performance lasting <30 s. The possible ergogenic effect is unlikely to be related to changes in blood glucose, sweetness or energy sensing mechanisms in the gastrointestinal tract.